Analyzing the Relationship Between Use of Internet and Value System of Youth and Teenagers (Case Study: Shiraz city) - ali rouhani; somayeh hashemi; masoud anbarlou (توسعه اجتماعی)
The number of internet users has been increased from three million people to more than 3 trillion people in two last decades. The increased use of internet among youth and teenagers has impressed many values, norms, manners, life styles, and features of them. Accordingly, this study has attempted to study the relationship between use of internet and value system of youth and teenagers. For this purpose, 400 adolescents (youth and teenagers) of Shiraz city were selected based on multi-stage cluster sampling and answered to the questions of researcher-made questionnaire. The dependent variable of the research included different categories and a range of values composed of eight categories namely native, national, global, religious, economic, scientific, social/cultural, and familial values. The use of internet also was analyzed in detail. The findings of the study showed that there is a meaningful relationship between use of internet and national, religious, global, economic and social/cultural values.